The impact of books on social inclusion and development and well‐being among children and young people with severe and profound learning disabilities: Recognising the unrecognised cohort. (7th February 2019) - Robinson, Deborah; Moore, Nicki; Harris, Catherine
Accessible Summary: This paper shows what people with learning disabilities can get out of enjoying books and reading even when they cannot read words easily. The writers think about how people with learning disabilities can be helped to enjoy books. They say that this can happen through reading with other people, enjoying lots of activities about books and making books part of their daily routine. The writers also think about the way that books and stories help us to learn about the world and the people in it. The writers are annoyed about the way that enjoyment of books by people with learning disabilities has been ignored by people. This matters to people with learning difficulties because enjoying books, even when we cannot read words easily, can give us good feelings and help us to learn and develop. Abstract: This paper presents the findings of an original research project commissioned by BookTrust, a respected UK charity that gifts books to children, young people (CYP) and their families. It explored the impact and modus of pleasurable engagement with books among CYP with severe and profound learning disabilities and applied a critical, phenomenological stance on what it means to read through drawing on "inclusive literacy" as a conceptual framework. Data were collected from four local areas in England and included 43 CYP aged 4–14. In keeping with a phenomenological stance, it employed interpretivist methods involving 13 deep‐level interviews with families to include observations and structured play; 13 observations of CYP sharing books with others in home, play or school settings, and interviews with 27 practitioners working in a range of organisations (e.g., Portage service and advisory teams). Findings were that books had a positive impact on well‐being, social inclusion and development. CYP were engaged in enjoying the content of books through personalisation, sensory stimulation, social stimulation and repetition. This affirmed the theoretical and practical approaches espoused by "inclusive literacy" but made a critical and original contribution to our understanding of the special place that books occupy as ordinary artefacts of literary citizenship among this cohort. The benefits of volitional reading among CYP who do not have learning disabilities are well known, but the authors urge publishers and policymakers to recognise CYP with severe and profound learning disabilities as equally important, active consumers of books who have much to gain from reading for pleasure.